CGDB: a database of membrane protein/lipid interactions by coarse-grained molecular dynamics simulations. - Chetwynd, A; Scott, K; Mokrab, Y; Sansom, MS (2008)
Membrane protein function and stability has been shown to be dependent on the lipid environment. Recently, we developed a high-throughput computational approach for the prediction of membrane protein/lipid interactions. In the current study, we enhanced this approach with the addition of a new measure of the distortion caused by membrane proteins on a lipid bilayer. This is illustrated by considering the effect of lipid tail length and headgroup charge on the distortion caused by the integral membrane proteins MscS and FLAP, and by the voltage sensing domain from the channel KvAP. Changing the chain length of lipids alters the extent but not the pattern of distortion caused by MscS and FLAP; lipid headgroups distort in order to interact with very similar but not identical regions in these proteins for all bilayer widths investigated. Introducing anionic lipids into a DPPC bilayer containing the KvAP voltage sensor does not affect the extent of bilayer distortion.